Assistance of Class Action Research (Car) And Open Journal System (OJS Teachers for Sports and Health Physical Education - Destriana; Silvi Aryanti; Arizky Ramadhan (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2021)
The purpose of this community service is to provide assistance in writing classroom action research (CAR) and the open journal system (OJS) for physical education teachers in Ogan Ilir District. This community service was carried out online from 20-22 November 2020. The number of participants in this service was 75 physical education teachers consisting of elementary school, junior high school, high school. The methods used in the implementation of the service are lectures, questions and answers, demonstrations, and practice. To see the results of assistance, use a questionnaire to see to what extent this assistance is useful. The results obtained in mentoring the writing of CAR and OJS were that on average 91.8% of participants could understand the writing of CAR and could use OJS. The results of this service are expected to increase competence as a teacher so that it can improve and improve the quality of physical education learning, especially in Ogan Ilir Regency